1977
DOI: 10.1111/j.1471-4159.1977.tb10623.x
|View full text |Cite
|
Sign up to set email alerts
|

Studies on Mevalonate Kinase, Phosphomevalonate Kinase and Pyrophosphomevalonate Decarboxylase in Developing Rat Brain

Abstract: Abstract— We have in the present study investigated the properties of mevalonate kinase, phosphomevalonate kinase and pyrophosphomevalonate decarboxylase in the 105,000 g supernatant fractions from rat brain, and determined whether the activities of these enzymes change during brain development. All three enzymes in brain showed a specific requirement for ATP for optimal activity. The presence of Mg2+ as divalent cation was also required for optimal activity of mevalonate kinase and phosphomevalonate kinase. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1981
1981
2002
2002

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 16 publications
0
13
0
Order By: Relevance
“…Thus, pH values observed for optimal activity are higher than those reported for both kinases in mammal tissues [8,9]. How ever, the pH profile of MVAPP decarboxyl ase from chick brain is similar to that re ported from rat brain [14], On the basis of these results, the hypothe sis about a main role of the reactions of MVA phosphorylation and decarboxylation in the cholesterol biosynthesis may be corrobo rated.…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Thus, pH values observed for optimal activity are higher than those reported for both kinases in mammal tissues [8,9]. How ever, the pH profile of MVAPP decarboxyl ase from chick brain is similar to that re ported from rat brain [14], On the basis of these results, the hypothe sis about a main role of the reactions of MVA phosphorylation and decarboxylation in the cholesterol biosynthesis may be corrobo rated.…”
Section: Discussionmentioning
confidence: 72%
“…Ramachandran and Shah [14] reported that the use of different buffering compo nents to obtain the necessary pH range did not influence the activities of any of the three enzymes in rat brain. Nevertheless, our re sults indicate the existence of differences in the amount of MVAP and MVAPP found when two different types of buffers were used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Mevalonic acid 5-phosphate is further phosphorylated to yield MVA 5-pyrophosphate; the reaction is catalyzed by 5-phosphomevalonate kinase (EC 2.7.4.2). This reaction is freely reversible in animal systems (395,396,397). The product of the reaction has been demonstrated in a number of higher plants (377,380,(384)(385)(386); however, the specific kinase has only been detected in the latex of Heveu brasiliensis (398) and in leaves of Nepera cararia (399).…”
Section: Formation Of Precursorsmentioning
confidence: 97%